Crescimento de mudas micropropagadas da bananeira cv. Nanicão, em diferentes substratos e fontes de fertilizante - Nomura, Edson Shigueaki; Lima, Juliana Domingues [UNESP]; Garcia, Valeria Augusta; Rodrigues, Domingos Savio (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
With the objective of evaluating the effect of different substrates combined with fertilizers in the growth of micropropagated seedlings of Cavendish banana (Musa spp. AAA), ail experiment was conducted in a randomized block design, in a 5 x 3 factorial scheme, with four repetitions. The substrates used were: S1 - subsoil land + carbonized rice hull + Rendmax Floreira (R); S2 - subsoil land + carbonized rice hull + Organifol (R); S3 - subsoil land + carbonized rice hull + Organifol (R) 9% SiO; S4 - Technes Vivatto (R); S5 - thick sand + carbonized rice hull + Rendmax Floreira (R). The fertilizer sources were: SA - without fertilizer; LL - slow-release fertilizer - Osmocote (R) 3M 14-14-14 (5.0 kg m(-3)) inixed in the substrate; and LN - normal-release fertilizer, 14-14-14 (7.5 g seedling(-1)) applied in covering. The height, collar diameter, leaf number, leaf area and dry matter were determined. Based on the differences of growth, substrates S 1, S2, S3 and S4 can be used with fertilizer 14-14-14, with slow (5.0 kg m(-3)) or normal (7.5 g seedling(-1)) release of nutrients.
Growth of micropropagated cavendish banana seedlings in different substrates and fertilizer sources
Keywords: Musa spp.; acclimatization; seedling production